An Analysis of Directive Speech Acts in The Up (2009) Movie - Widianingsih, Ayang Winda Sri; Mustika, Rispa; Nugraha, Salsa (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This research discussed about the analysis of directives type of speech act theory used in the Up (2009) movie. This research revealed the application of directives types of speech act that found in the Up (2009) movie. The document analysis approach was used in this study to gather data. The researcher chose this film as the subject of the study because it is intriguing and has numerous moral lessons. This film's themes include love, relationships between people, hope, and dreams. As the result, it was found that were 57 utterances of directive speech acts in the Up (2009) movie. From the 57 data that researcher collected, the main characters most expressed the  command type of directives speech act. They are 38 commands, 3 suggestions, 3 requests, 6 orders, forbidding. Based all the data above, it can be concluded the most used directives speech act found in this data was command.